A new preparation method of graphite cones from polycyclic aromatic hydrocarbons/polyimide composite carbon fibers. (30th August 2022) - Liu, Yuhong; Liu, Xueping; Ma, Zhaokun; He, Yan; Zhang, Xingwei
Abstract: Graphite cone and whisker are a kind of non-planar graphite crystal material with a large length-diameter ratio, exhibiting extremely high mechanical and conductive properties. Although they have been discovered and studied for many years, their formation mechanism is still unclear. They have not been prepared and applied on a large scale because the preparation methods involve some extremely harsh conditions such as high temperature and high-pressure arc discharge, etc. Herein, a simple and novel method to fabricate graphite cones is presented. A large number of spiral graphite cones (SGCs) are grown in situ from the surface of polycyclic aromatic hydrocarbons/polyimide (PAH/PI) composite carbon fibers without catalyst during graphitization. The SGCs are formed by two-dimensional graphene consisting of sp 2 hybrid carbon atoms, and the angle between the carbon layer of SGC and the graphite cone axis is approximately 67.5°. The formation mechanism of SGCs from the special organic fibers is also speculated and presented. This new preparation method provides great possibilities for large-scale material production and the widespread applications of graphite cones in the future. Graphical abstract: Image 1